Gestão democrática na escola pública : questões e posssibilidades - Freitas, Solange Rodrigues de (2007)
The present text is resulted of a work of research carried through on the possibilities and limits gifts in the construction of a participative popular democracy, in the interior of a public school of the Municipal System of Education of the city of Juiz de Fora (MG), with the objective of: ) to analyze and external condicionantes of the participation of the pertaining to school community; b) to analyze the participative relation between communitarian school and social organizations; c) to reflect on the type of participation practiced in the interior of the school and its entorno, tied with the social political context of the country, which is its process of democratic construction; d) to explicit aspects that can extend the participative quarrel politician of the popular classrooms in the routes of the public education. Relation to the methodological aspect, he seemed us that the made right option more would be a qualitative inquiry, searching to examine the multiple aspects involve the question of the participation of the pertaining to school community, beyond organizations of the popular civil society, specifically the Union of the Professors of Juiz de Fora (Sinpro-JF). As result of this research, he was observed that despite the limitations imposed for the liberal model of democracy, hegemonic in our society, democratic practical possibilities of construction of popular exist in the interior of the school, from administrations compromised to a public education of quality, as well as, perspectives of construction of a democratic space of dispute of projects participation inside of the school, from the practical-educative one of the Sinpro, when this if considers to argue with the professors and communities, educational politcs, in intention to fortify the construction of an alternative educational project for the popular classrooms.